Rural Development and Agricultural Growth in Indonesia, the Philippines and Thailand - Akiyama, Takamasa; Larson, Donald F. (Canberra: Asia Pacific Press, 2013)
Understanding economic growth is central to the study of development. Rural economic growth is an important aspect of economic growth. Historically, rural agriculture has employed most people in most countries, and continues to do so today. Nevertheless, the casual relationship between economic growth and growth in agriculture remain poorly understood. This volume focuses on economic growth in the agriculture sectors of Indonesia, the Philippines and Thailand. Starting from similar positions, the agriculture sectors of these economies have diverged considerably over the last 40 years. This volume investigates the ways in which policy, institutions, investments, resource constraints and the reallocation of agricultural labor have driven this divergence. It volume documents the interplay of endowments, technology, the accumulation of productive factors, policy, and advocacy in the rural sectors of these three countries. It contributes in its own ways to an explanation of the past. Good policy rests on an understanding of successes and failures in the past. This book is a critical contribution to such an understanding.